2023
DOI: 10.3390/foods12020296
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Piperine on Saltiness Perception

Abstract: Chemical irritants, like piperine, have the potential to increase human perception of tastes and odours, including saltiness. This cross-modal interaction could help the food industry develop new salt-reduced food products that maintain their salty taste. The objective of this study was: firstly, to determine the detection threshold of piperine (n = 72), secondly to evaluate piperine’s influence on saltiness perception in model solutions (n = 78), and lastly to identify piperine’s effect on sensory perception … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 56 publications
0
9
0
Order By: Relevance
“…A study by Nasrawi & Pangborn (1989) found that the burning effect of capsaicin was delayed by the addition of 0.2% xanthan gum due to the viscosity it imparts. This result was also found in a past study investigating the burning intensity of piperine and xanthan gum solutions (Moss et al ., 2023). Results clearly showed that all solutions containing AITC (with and without NaCl and/or xanthan gum) scored significantly higher ( P < 0.05) for bitterness than solutions without AITC, which is an established descriptor for AITC (Sindhu et al ., 2012).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…A study by Nasrawi & Pangborn (1989) found that the burning effect of capsaicin was delayed by the addition of 0.2% xanthan gum due to the viscosity it imparts. This result was also found in a past study investigating the burning intensity of piperine and xanthan gum solutions (Moss et al ., 2023). Results clearly showed that all solutions containing AITC (with and without NaCl and/or xanthan gum) scored significantly higher ( P < 0.05) for bitterness than solutions without AITC, which is an established descriptor for AITC (Sindhu et al ., 2012).…”
Section: Resultsmentioning
confidence: 99%
“…The pungency of AITC may enhance the perception of salt flavour, as was found for capsaicin (Gilmore & Green, 1993; Narukawa et al ., 2011; Li et al ., 2017) by increasing consumers' sensitivity to other tastants and could modify the neural processing of the salty taste (Li et al ., 2017). This result was also found with piperine (Moss et al ., 2023). Furthermore, trigeminal sensations could induce new sensations which help improve the overall taste and flavour perception of the food time (Cayeux et al ., 2023).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…While some chemical compounds in foods have been researched and exhibit sensory transference properties, such as capsaicin in chili peppers, other compounds such as piperine in pepper have not been studied as thoroughly (Eib et al, 2021; Haq et al, 2021; Srinivasan, 2007; Utama‐ang et al, 2020). Only a few studies have looked at saltiness perception associated with piperine (Montero & Ross, 2022; Moss et al, 2023). Furthermore, of the few studies conducted on black pepper, there are no studies assessing the perception of white pepper.…”
Section: Introductionmentioning
confidence: 99%